Evaluation of Mangrove Ecosystem Quality in Bawean Island, East Java Using Phytoplankton as Bioindicators - Salsabila, Qathrunnada; Retnaningdyah, Catur; Hakim, Luchman (Jurnal Ilmiah Perikanan dan Kelautan, 2024)
Graphical Abstract Highlight Research Highlights from this results research: Restoration is a method to restore degraded mangrove ecosystems The success of restoration is measured by improvements in ecosystem services such as water quality, mangrove diversity, phytoplankton community structure and diversity Phytoplankton as bioindicator of water quality Anthropogenic activities are the main factor causing degradation of mangrove ecosystems Abstract The mangrove ecosystems in Bawean Island are degraded due to anthropogenic activities and land conversion. Plantation has carried out periodic which was continued in several mangrove ecosystems. This study was conducted to evaluate the physicochemical water quality of several mangrove ecosystems in Bawean Island, and phytoplankton as bioindicators. The evaluation of mangroves in Bawean Island was carried out at 11 locations based on different naturalness and human activities surrounding. The physical and chemical parameters of water observed were air temperature, water temperature, pH, TSS, dissolved oxygen (DO), biochemical oxygen demand (BOD), salinity, conductivity, nitrate, and orthophosphate. Community structure and plankton diversity measured include the Importance Value Index (IVI), Shannon-Wiener diversity index (H'), Simpson dominance index (Id), evenness index (E), trophic diatom index (TDI), and pollution tolerant value (% PTV). The physical parameters of water chemistry show that it meets the quality standards based on Indonesian Government Regulation No. 22 of 2021 except for nitrate and orthophosphate, but it is still under plankton tolerant. A total of 63 species from 7 phytoplankton classes were found based on the importance value index. Based on the TDI index, mangrove ecosystems Sawahmulya, Sidogedungbatu, Hijau Daun, Pamona, Pasir Putih, Sungai Rujing, Bangsal, Jherat Lanjheng, and Lebak were classified as eutrophic while Pulau Cina and Dekatagung were hyper-eutrophic. Based on %PTV, the Hijau Daun mangrove is the best mangrove ecosystem while other mangroves were classified as moderate and heavily level polluted.